Penegakan Hukum Terhadap Jual Beli Pakaian Bekas Impor â€œThriftingâ€ Di Wilayah Banyumas - Yulianti, Tri; Marlia Hafny Afrilies; Maya Ruhtianti (Fakultas Hukum Universitas Islam Batik Surakarta, 2024)
This study examines the buying and selling of imported used clothing in the Banyumas area which aims to identify and analyze law enforcement against the buying and selling of imported used clothing in the Banyumas area, and to identify and analyze the obstacles to law enforcement against the buying and selling of imported used clothing